Recensiones: Julian of Toledo. Prognosticum futuri saeculi - Foreknowledge of the World to come ; Domingo M. Basso, O.P., Moral Fundamental - Capboscq, Alberto Carlos; Juárez, Guillermo Andrés (Studium. Filosofía y Teología, 2011)
Julian of Toledo. Prognosticum futuri saeculi - Foreknowledge of the World to come, translated, edited, and introduced by Tommaso Stancati O.P., Foreword by His Eminence Cardinal Antonio Cañizares Llovera Archbishop of Toledo, Primate of Spain (Ancient Christian Writers 63), New York/Manwah, NJ, The Newmann Press, 2010; 15 + 608 pp. (Alberto Carlos Capboscq) Domingo M. Basso, O.P., Moral Fundamental. Buenos Aires, EDUCA, 2011, 514 pp., ISBN: 978-987-620-187-2. (Guillermo Andrés Juárez)